2023
DOI: 10.3390/nu15204392
|View full text |Cite
|
Sign up to set email alerts
|

The Nephroprotective Effect of Cornelian Cherry (Cornus mas L.) and Rowanberry (Sorbus aucuparia L.) in Gentamicin-Induced Nephrotoxicity on Wistar Rats with Emphasis on the Evaluation of Novel Renal Biomarkers and the Antioxidant Capacity in Correlation with Nitro-Oxidative Stress

Mara Aurori,
Sanda Andrei,
Alexandra Iulia Dreanca
et al.

Abstract: In spite of its well-known nephrotoxicity, gentamicin is nonetheless routinely used in humans and animals. However, no adjuvant treatments have been implemented to mitigate this harmful effect. Given this concern, medicinal plants represent a significant reservoir of natural antioxidants that could potentially reduce the renal oxidative stress induced by gentamicin. Therefore, the main objective of this research was to investigate the nephroprotective properties of Cornus mas and Sorbus aucuparia fruits in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The differences in antioxidant activity among the tested samples resulted from different contents of biologically active compounds, which resulted from the use of different extractants during The antioxidant effect of the tested extracts and hydrogels is certainly related to the antioxidant activity of the phytochemicals contained in dogwood fruits. The chemical compounds detected during the chromatographic analysis may support the defense against high levels of ROS by influencing the activity of enzymes such as superoxide dismutase, catalase or glutathione peroxidase [27,28]. The antioxidant effect of the tested extracts may also be the result of inhibiting or quenching free radical reactions in the tested cells.…”
Section: Intracellular Ros Levels In Skin Cellsmentioning
confidence: 99%
“…The differences in antioxidant activity among the tested samples resulted from different contents of biologically active compounds, which resulted from the use of different extractants during The antioxidant effect of the tested extracts and hydrogels is certainly related to the antioxidant activity of the phytochemicals contained in dogwood fruits. The chemical compounds detected during the chromatographic analysis may support the defense against high levels of ROS by influencing the activity of enzymes such as superoxide dismutase, catalase or glutathione peroxidase [27,28]. The antioxidant effect of the tested extracts may also be the result of inhibiting or quenching free radical reactions in the tested cells.…”
Section: Intracellular Ros Levels In Skin Cellsmentioning
confidence: 99%
“…Aurori et al reported a protective effect of dogwood fruits (at a dose of 40 mg/kg) on renal tubules in studies on Wistar rats [39]. In their study on kidney epithelial cells (Vero), Yarim et al also showed that a cornelian fruit extract (in a concentration range of 1-100 µg/mL) protected cells against in vitro oxidative damage caused by cisplatin [40].…”
Section: Discussionmentioning
confidence: 98%
“…Lam et al [18] evaluated the effects of dihydro-resveratrol, which is distributed in plants of the Orchidaceae family and Cannabis sativa L., on insulin resistance, lipid accumulation and adipocyte differentiation in a high-fat-diet-induced mouse model; the primary mechanism comprised a reduction in the aggravation of oxidative stress via the modulation of the Nrf2-related antioxidative cascade. Wang et al [19] revealed that Glabridin, an isoflavone extracted from Licorice root, alleviated ethanol-induced liver injury damage via a reduction in oxidative stress and inflammation through the p38 MAPK/Nrf2/NF-κB Aurori et al [20] demonstrated that the nephrotoxicity induced by gentamicin can by mitigated via antioxidant therapy that utilizes an extract prepared from the fruits of Cornus mas and Sorbus aucuparia.…”
mentioning
confidence: 99%